Viability of Cryopreserved Probiotic Strains of Microorganisms Immobilized in Alginate Gel Supplemented with Disaccharides - Potapov, Volodymyr A.; Biliy, Dmytro V. (Problems of Cryobiology and Cryomedicine, 2019)
Probl Cryobiol Cryomed 2019; 29(2): 176.